2016
DOI: 10.1103/physrevlett.117.087402
|View full text |Cite
|
Sign up to set email alerts
|

Tunable Weyl Points in Periodically Driven Nodal Line Semimetals

Abstract: Weyl semimetals and nodal line semimetals are characterized by linear band touching at zero-dimensional points and one-dimensional lines, respectively. We predict that a circularly polarized light drives nodal line semimetals into Weyl semimetals. The Floquet Weyl points thus obtained are tunable by the incident light, which enables investigations of them in a highly controllable manner. The transition from nodal line semimetals to Weyl semimetals is accompanied by the emergence of a large and tunable anomalou… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
162
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 216 publications
(167 citation statements)
references
References 103 publications
4
162
0
1
Order By: Relevance
“…Other recent Floquet-topological phenomena include nodal rings, 15 type-II Floquet-Weyl semimetals 16 , carbon nanotubes 17 and soundwaves 18 among others.…”
Section: -14mentioning
confidence: 99%
“…Other recent Floquet-topological phenomena include nodal rings, 15 type-II Floquet-Weyl semimetals 16 , carbon nanotubes 17 and soundwaves 18 among others.…”
Section: -14mentioning
confidence: 99%
“…The observation of such oscillations could be a direct proof of the existence of the chiral nodes, but since the momentum separation of the chiral nodes remains fixed for a given material, it is not likely to be usable as a tuning parameter. On the other hand, it has also been understood recently how time periodic perturbations can affect the WSM [37][38][39][40][41][42] , and in particular, how a high frequency incident elliptically polarized light can slightly modify the position of the effective chiral nodes of the WSM 43 . This provides the possibility that the external parameters controlling the perturbation can serve as tuning parameters in adjusting the separation of the chiral nodes.…”
mentioning
confidence: 99%
“…A typical example is the generation of a Weyl point from a Dirac semimetal [42][43][44][45] . It is shown that a Weyl node can also be generated by applying photoirradiation to a loop nodal semimetal 46,47 . In this paper, we first propose a simple scheme to construct models for crossing-line nodal semimetals.…”
mentioning
confidence: 99%